The Frontal Sinus Dimensions in Mouth and Nasal Breathers in Iraqi Adult Subjects - Mohammed , Shahbaa A; Al-Sheakli , Iman I; Taha , Shaymaa Sh (Journal of the college of dentistry, 2013)
of this study were to determine the gender difference in each group, to compare the frontal sinus area between mouth breather and nasal breather group, and to verify the presence of correlation between the frontal sinus area and the cephalometric skeletal measurements used in this study. Materials and Methods: Cephalometric radiographs were taken for 60 adults (30 mouth breathers and 30 nasal breathers) age range (18-25), for each group 15 males and 15 females, in the orthodontic clinic in the college of Dentistry at Baghdad University. The control group (nasal breather) with skeletal class I and ANB angle ranged between 2-4º, and have clinically class I occlusion. The cephalometric measurement for each group were taken, the cephalometric radiographs were analyzed by using AutoCAD 2007 program. Results and Conclusions: In comparison to nasal breather the mouth breather has larger Gonial angle giving a tendency to posterior rotation with growth of the mandible. The mouth breather has less maxillary length than the nasal breather. No effect of gender in mouth breather on gonial, SNA and SNB angles, no effect of gender in nasal breather on gonial angle, while the other cephalometric measurements were higher in males than females in each group. The mouth breather showed more anteroposterior extent of anterior cranial base; also the mouth breather show an increase in all facial height than the nasal breathers, the frontal sinus area is smaller in mouth breather than in nasal breather. The frontal sinus area showed correlation for both groups (Mouth and nasal breather) with maxillary Length, mandibular length, ramal length, S-N length, TAFH, UAFH, LAFH, TPFH, LPFH, and UPFH. There is only correlation of frontal sinus with the SNA and SNB angles in nasal breather and no significant correlation for both groups with the gonial angle.